2013
DOI: 10.1111/exd.12287
|View full text |Cite
|
Sign up to set email alerts
|

Cycling up the epidermis: reconciling 100 years of debate

Abstract: There is likely general consensus within the skin research community that cell cycle control is critical to epidermal homeostasis and disease. The current predominant model proposes that keratinocytes switch off DNA replication and undergo cell cycle and cell growth arrest as they initiate terminal differentiation. However, this model cannot explain key physiological features of the skin, mainly why squamous differentiation prevails over proliferation in benign hyperproliferative disorders. In recent years, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 91 publications
1
39
1
Order By: Relevance
“…Thus, keratinocytes continue to replicate their DNA without equivalent execution of cell division as they differentiate, resulting in the production of large cells with increased DNA content as cells progress through the suprabasal layers. 2,64,65 In addition, the inhibition of mitotic kinases such as CDK1, Aurora kinase B, or PLK1 triggers polyploidization and differentiation of primary keratinocytes. 64,65 These published results are very consistent with our findings that in addition to producing binucleated cells with ≥4n DNA content (Figure 1), AREG silencing leads to the accumulation of flattened keratinocytes that are strongly engaged in terminal differentiation (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, keratinocytes continue to replicate their DNA without equivalent execution of cell division as they differentiate, resulting in the production of large cells with increased DNA content as cells progress through the suprabasal layers. 2,64,65 In addition, the inhibition of mitotic kinases such as CDK1, Aurora kinase B, or PLK1 triggers polyploidization and differentiation of primary keratinocytes. 64,65 These published results are very consistent with our findings that in addition to producing binucleated cells with ≥4n DNA content (Figure 1), AREG silencing leads to the accumulation of flattened keratinocytes that are strongly engaged in terminal differentiation (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…2 Epidermal growth factor receptor (EGFR) signaling is an important regulator of epidermal development and homeostasis 36 and plays an important role in the control of multiple keratinocyte functions including migration, 7,8 proliferation, 9 differentiation, 1012 survival 13,14 and activation of innate and adaptive immune responses. 1517 Deregulated EGFR signaling is a hallmark of epithelial cancer 18 , and EGFR is a validated target in several types of carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…In both mammals, there is a basal layer containing proliferative cells that give rise to keratinocytes. As the mitotic divisions from the basal layer push keratinocytes towards the surface of the skin, they differentiate and become polyploid by endomitosis or the endocycle (Figure 2C) [3032]. The junctions between polyploid keratinocytes have not been analyzed, but the presence of large cells, possibly connected into an envelope, could protect the underlying tissue layers.…”
Section: Overview Of Somatic Polyploidymentioning
confidence: 99%
“…It has been recently shown that an increase in ploidy due to a mitotic block is associated with terminal differentiation in human epidermis (Gandarillas and Freije, 2014; Zanet et al, 2010). Using fluorescence in situ hybridization (FISH) assays, we confirmed the presence of some polyploid cells in the suprabasal layers of mouse skin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several molecular mechanisms are instrumental for the control of the finely tuned balance between proliferation and differentiation, including genetic and epigenetic changes, transcriptional regulation, signalling cues and cellular interactions (Blanpain and Fuchs, 2009; Simpson et al, 2011). Moreover, recent reports show that a mitotic block coupled to an increase in ploidy is associated with epidermal differentiation (Gandarillas and Freije, 2014; Zanet et al, 2010). Indeed, a ploidy increase is linked to cell differentiation during the development of multiple organs (Lee et al, 2009; Orr-Weaver, 2015), but despite its relevance, the molecular mechanisms involved remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%